Rare Case of a Calcified Catheter-Related Sheath Embolizing to the Right Pulmonary Artery - Lee K. Rousslang; Jonathan R. Wood (Case Reports in Radiology)
Catheter-related sheaths, formerly known as “fibrin sheaths,” are the most common complications of central venous catheters. Although usually harmless, they can very rarely detach from the venous wall against which they were formed and embolize with effects ranging from subclinical embolisms to death. This rare occurrence has only been described a few times in the literature to date, and to our knowledge, the embolized sheath has never been directly visualized with CT. We report the case of catheter-related sheath embolization to the right pulmonary artery in a child, as confirmed on CT.